Pengaruh Kompensasi, Motivasi, dan Budaya Organisasi Terhadap Pada PT. Nasmoco Pemuda Semarang - Triana, Nani; Soewarso, Soewarso; Wijayanto, Andi (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2012)
Employee's performance is not optimal due to several factors, including compensation, motivation and organizational culture. PT. Nasmoco Pemuda is an enterprise engaged in commerce or services. In its development, the volume of sales from year to year has been fluctuating and declining employee performance. The purpose of this study is to demonstrate the influence of compensation, motivation and organizational culture on employee performance. Type of research is explanatory research. The hypothesis is that the compensation (X1), motivation (X2), organizational culture (X3) have a significant impact on employee performance (Y). The conclusion of this study is compensation, motivation, and organizational culture at PT. Nasmoco Pemuda classified as good. The test results show that compensation, motivation, and organizational culture have a significant influence on employee performance.